2020
DOI: 10.1080/24733938.2020.1782458
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between eccentric hamstring strength and dynamic stability in elite academy footballers

Abstract: Objectives: Previous research describes dynamic stability and functional strength as key aetiological risk factors associated with lower limb non-contact musculoskeletal injury. Due to the multi factorial nature of injury risk, relationships between the two factors will inform injury management and training design.Methods: Fifty-nine elite academy footballers from two English premier league category 1-status academies completed the study. All players completed measures of eccentric hamstring strength and dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Recent literature has identified that increases in flexibility have been associated with reductions of functional strength through range, and thus increased injury risk (Opar, 2013;Timmins et al, 2016). This body of work highlighted changes in muscle architecture as a key aetiological factor, with o representing a metric to provide insight into this factor within the present study (Greig., 2008;Rhodes et al, 2018;Rhodes et al, 2020). The present body of work identified no significant changes in functional strength metrics and break angle despite increases in flexibility.…”
Section: Discussionmentioning
confidence: 54%
“…Recent literature has identified that increases in flexibility have been associated with reductions of functional strength through range, and thus increased injury risk (Opar, 2013;Timmins et al, 2016). This body of work highlighted changes in muscle architecture as a key aetiological factor, with o representing a metric to provide insight into this factor within the present study (Greig., 2008;Rhodes et al, 2018;Rhodes et al, 2020). The present body of work identified no significant changes in functional strength metrics and break angle despite increases in flexibility.…”
Section: Discussionmentioning
confidence: 54%
“…Reasons for this are unclear, however, it is suggested this could potentially be associated with the bilateral nature of the exercise (Opar et al, 2013;Timmins et al, 2015) and the larger group of muscle recruitment required to perform the exercise (Wiesinger et al, 2020). This may highlight deficiencies in elite youth footballers that could contribute to sustaining lower limb injury (Rhodes et al, 2020a). Practitioners and future research should consider electromyographic analysis of the musculature during performance of the test to identify asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…Each trial was recorded from the sagittal plane using a Canon XA35 camera at 50 Hz. The camera was placed on a fixed stand set 3 m away and 0.5 m from the floor (Rhodes et al, 2020a). Each participants' Ɵ (lowest, closest to the floor) was calculated by using reflective markers placed on the skin of the anatomical landmarks previously set with the best repetition used for the purpose of the research (Rhodes et al, 2020a), which included; right greater trochanter, lateral femoral condyle, and lateral malleolus (Lee, Mok, Chan, Yung, Chan, 2017).…”
Section: Eccentric Hamstring Strengthmentioning
confidence: 99%
See 2 more Smart Citations